A pegada ecológica como instrumento de avaliação ambiental para a cidade de Londrina - Cristiane Kleba Lisboa; Mirian Vizintim Fernandes Barros (Confins)
In the definition of environmental evaluation tools and life quality, the Ecological Footprint, proposed by William Rees and Mathis Wackernagel (1996), it has been used as an important indicator of environmental and sustainability pointer at different analysis scales. In the current article it was used the Ecological Footprint for an urban analysis, evaluating the impacts generated by the city of Londrina-PR and by its citizens. The footprint was calculated through nine variables, qualitative and quantitative, analyzed from the Geographic Information System GIS.